2013
DOI: 10.2134/jeq2012.0163
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Stability, and Plant Effects of Kiln-Produced Wheat Straw Biochar

Abstract: Biochar is a promising technology for improving soil quality and sequestering C in the long term. Although modern pyrolysis technologies are being developed, kiln technologies often remain the most accessible method for biochar production. The objective of the present study was to assess biochar characteristics, stability in soil, and agronomic effects of a kiln‐produced biochar. Wheat‐straw biochar was produced in a double‐barrel kiln and analyzed by solid‐state 13C nuclear magneticresonance spectroscopy. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…As biochar is a material with high C content, some farmers may be concerned that adding large amounts to their soils (the amount of biochar in BC25 applied in our experiment is 10 times that of yearly straw produced from the same land area) may lead to a microbial immobilization of N and, thus, reduce plant yields. While some studies have shown short-term N immobilization that restricts plant growth [62,63], we did not observe this under field conditions over four years where even the higher BC treatment did not reduce grain, straw yields, and grain protein or increase Microbal C or N. A lack of yield response after the biochar amendment concurs with other studies in boreal and temperate regions. Reference [64] found no yield differences in wheat or faba bean after applying spruce and pine biochar at 10 t ha −1 in a three-year field experiment in Finland and a similar absence of yield effect was found in a two-year field ring trial carried out in seven different countries in Northern Europe [65].…”
Section: Grain Yield and Qualitysupporting
confidence: 79%
“…As biochar is a material with high C content, some farmers may be concerned that adding large amounts to their soils (the amount of biochar in BC25 applied in our experiment is 10 times that of yearly straw produced from the same land area) may lead to a microbial immobilization of N and, thus, reduce plant yields. While some studies have shown short-term N immobilization that restricts plant growth [62,63], we did not observe this under field conditions over four years where even the higher BC treatment did not reduce grain, straw yields, and grain protein or increase Microbal C or N. A lack of yield response after the biochar amendment concurs with other studies in boreal and temperate regions. Reference [64] found no yield differences in wheat or faba bean after applying spruce and pine biochar at 10 t ha −1 in a three-year field experiment in Finland and a similar absence of yield effect was found in a two-year field ring trial carried out in seven different countries in Northern Europe [65].…”
Section: Grain Yield and Qualitysupporting
confidence: 79%
“…It was possible that the general lower leaf Ca and Mg concentrations we found in lettuce could be due to excess Zn in the biochars. O'Toole et al (2013) suggested that the Zn in galvanized metal containers used during their studies likely increased biochar Zn, which reduced plant Ca and Mg. However, we used ceramic bowls to make biochar, and, thus we did not have a metal container factor.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, O'Toole et al [37] reported on a pot experiment growing ryegrass under 4 rates of N fertiliser with 2 rates of a wheat-straw biochar (500-600 °C) and found foliar N concentrations were reduced, possibly due to adsorption or immobilisation of N being stimulated with biochar addition, but with unaffected yields. Kammann et al [16] also observed reductions in foliar N concentrations in a pot trial with a relatively nutrient-rich peanut hull biochar, but in this case the reduction likely resulted from increased N use efficiency since the authors reported biomass increases of up to 60%.…”
Section: Plant Nitrogen Response To Biochar Amendmentmentioning
confidence: 99%